A Practical Test of Distance Learning During the COVID-19 Lockdown - Hęclik, Karol; Dobrowolski, Lucjan; Jaromin, Marcin; Zarzyka, Iwona (International Journal of Research in E-learning, 2023)
The article describes the authors’ experience of distance learning at Rzeszow University of Technology during COVID-19 lockdown. The problems associated with the didactics in the pandemic period were discussed. They concerned hardware, software, and teaching rooms. Technical and organisational issues were discussed. The aspect of student involvement in the distance learning process and the learning outcomes achieved by the students was also addressed. Finally, the conclusions that emerged from this stage of work with students were presented, as well as suggestions related to the improvement of the distance learning process for the future.